Orbital fractures - Denia Morales Navarro (Editorial Ciencias Médicas, 2018)
Introduction: fractures of the orbit are common and difficult to manage. Objective: to carry out a bibliographic review on anatomical considerations, physiopathology, diagnosis, treatment and complications of orbital fractures. Methods: abibliographic review was carried out in September 2016. Journals of impact in the Web of Sciences (35 journals) were evaluated. The databases MedLine, PubMed and ScieELO were consulted with the descriptors: "orbital fracture," "treatment," and "epidemiology." Articles in English and Spanish language of the last 5 years were included. 127 articles were obtained. The study was circumscribed to 47. Analysis and integration of information: the orbit presents anatomical weakness in the floor and the medial wall, which causes greater affectation due to fractures. There are several theories that justify its onset. The diagnosis is based on clinical findings, including ophthalmological findings, and diagnostic aids, which allows choosing the therapeutic modality and avoiding complications. Conclusions: based on the mastery of anatomic and diagnostic methods, the management of these lesions has changed little in recent years. However, advances in orbital imaging, the introduction of intraoperative navigation systems, better surgical indications and implant designs have led to a reassessment of the therapeutic approach to orbital fractures. Keywords: bone fracture; diplopia; enophthalmia; orbit.